Shopping for Health: Guide to Frozen Meals - Sarah A. Glenny; Wendy J. Dahl (EDIS)
Busy schedules, limited cooking space, or a lack of kitchen equipment may limit what you eat at meals. But with the large variety of frozen meals that are now in grocery stores, it’s possible to expand your food options and still eat tasty and healthy meals. The key is to know what to look for when you are shopping. To learn how to choose delicious meals that meet your taste preferences and your health needs, read this 3-page fact sheet written by Sarah A. Glenny and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, January 2012.